Benefits and cultural adaptations of psychosocial interventions for parents and their children with intellectual disabilities in low‐and middle‐income countries: A systematic review. Issue 2 (30th November 2020) - Susanty, Dessy; Noel, Pia; Sabeh, Meta Saraswati; Jahoda, Andrew
Abstract: Background: Evidence and awareness of the importance of culturally adapting psychosocial interventions is growing. The aim of this paper is to systematically review studies on cultural adaptations of psychosocial interventions for parents and their children with intellectual disabilities, in low‐ and middle‐income countries. Methods: Studies were identified through electronic databases and searching bibliographies. The quality and cultural adaptations of thirteen studies focusing on parental trainings were analysed using standardised tools and frameworks. Results: Findings suggest interventions reduce the risk of depression and stress and increase coping strategies and positive perceptions of family functioning. Parenting skills training may improve parent–child interactions and child development. However, these benefits should be interpreted cautiously due to methodological shortcomings. Most studies described efforts to make appropriate cultural adaptations to the interventions, but these adaptations were not comprehensive. Conclusion: High‐quality cultural adaptations are crucial to providing meaningful interventions in different parts of the world.